Positive plate and battery

By using a three-dimensional network skeleton in the positive electrode sheet of the lithium-ion battery, the problems of reduced transmission rate and insufficient toughness caused by the increase in the electrode surface density are solved, and higher cycle performance and safety performance are achieved.

CN119650578AActive Publication Date: 2025-03-18ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411771730.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the increase in the electrode surface density leads to a decrease in the transmission rate of electrons and lithium ions, and insufficient toughness, resulting in an increase in cyclic expansion rate, deterioration of high-temperature performance and attenuation of low-temperature performance.

Method used

A positive electrode sheet including a stereo network skeleton is used, which is formed of a conductive adhesive, which comprises a carbon nanotube and an adhesive layer on its surface. The adhesive layer contains an ester group, an amine group and a silane group, and the quantity ratio thereof is controlled to improve toughness and conductivity.

Benefits of technology

It improves the toughness and conductivity of the positive electrode sheet, enhances the transmission rate of lithium ions and electrons, reduces the cyclic expansion rate of the battery, and improves the cyclic performance and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650578A_ABST
    Figure CN119650578A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a positive plate and a battery comprising the positive plate. The positive plate comprises a positive current collector and a positive active material layer located on the surface of one side or two sides of the positive current collector, the positive active material layer comprises a three-dimensional network skeleton and a positive active material located in the three-dimensional network skeleton, and the three-dimensional network skeleton is formed by a conductive binder; the conductive adhesive comprises a carbon nanotube and an adhesive layer located on at least part of the surface of the carbon nanotube, the adhesive layer comprises an ester group, an amino group and a silane group, and the ratio of the number of the amino group and / or the silane group to the number of the ester group is (3-6): 1. The positive plate disclosed by the invention has relatively high toughness and is not easy to break, and meanwhile, the wettability and the conductivity of an electrolyte on the positive plate can be improved, so that the transmission rate of lithium ions and electrons in the positive plate is improved, the cyclic expansion rate of the battery is further reduced, and the cycle performance and the safety performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet and a battery comprising the positive electrode sheet. Background Art

[0002] In recent years, with the steady development of the lithium-ion battery industry, higher energy density lithium-ion batteries have become a hot topic of extensive research. The current technology mainly increases the surface density of the pole piece to improve the volume energy density of the lithium-ion battery. With the increase in the surface density of the pole piece, a series of problems will arise, such as poor toughness of the pole piece, and obstruction of lithium ion and battery transmission. Summary of the invention

[0003] Research has found that when the surface density of the electrode increases, on the one hand, it will lead to a decrease in the transmission rate of electrons in the electrode, and at the same time, it will also lead to a decrease in the transmission rate of lithium ions in the electrode. This is because as the thickness of the electrode of the lithium-ion battery cell increases, the electrode will not be sufficiently wetted in the electrolyte, resulting in a decrease in the transmission rate of lithium ions, slowing down the desolvation kinetics of lithium ions at low temperatures, and increasing the diffusion resistance of lithium ions in the solid electrolyte interface (CEI), resulting in lithium precipitation and purple spots in the lithium-ion battery, causing irreversible lithium loss, thereby affecting the electrochemical performance of the lithium-ion battery, and causing the lithium-ion battery to have an increased cycle expansion rate, deteriorated high-temperature cycle performance, and rapid low-temperature cycle attenuation; on the other hand, excessively thick electrode sheets will lead to insufficient toughness of the electrode sheets after rolling, resulting in problems such as inability to wind or winding breakage, increasing safety risks.

[0004] In order to solve the problems of poor toughness of thick electrode sheets and obstructed transmission of electrons and lithium ions in thick electrode sheets in the prior art, the present invention provides a positive electrode sheet and a battery including the positive electrode sheet. The positive electrode sheet of the present invention has high toughness and is not prone to breaking. At the same time, it can improve the wettability and conductivity of the electrolyte to the positive electrode sheet, thereby increasing the transmission rate of lithium ions and electrons in the positive electrode sheet, thereby reducing the cycle expansion rate of the battery, and improving the cycle performance and safety performance of the battery.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a positive electrode sheet, wherein the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer located on one side or both sides of the positive electrode collector, the positive electrode active material layer includes a three-dimensional network skeleton and a positive electrode active material located in the three-dimensional network skeleton, the three-dimensional network skeleton is formed by a conductive adhesive, the conductive adhesive includes carbon nanotubes and a bonding layer located on at least a portion of the surface of the carbon nanotubes, the bonding layer includes an ester group, an amine group and a silane group, wherein the ratio of the number of the amine groups and / or the silane groups to the number of the ester groups is (3-6):1.

[0006] A second aspect of the present invention provides a battery, which includes the positive electrode sheet described in the first aspect of the present invention.

[0007] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0008] The positive electrode active material layer of the positive electrode sheet of the present invention includes a three-dimensional network skeleton, which is formed by a conductive adhesive. The conductive adhesive includes carbon nanotubes and an adhesive layer located on at least a portion of the surface of the carbon nanotubes. The two ends of the carbon nanotubes can be evenly embedded in the positive electrode sheet to construct a conductive network to increase the electron transmission rate and improve the battery's cycle performance. The ester group in the adhesive layer can increase the toughness of the three-dimensional network skeleton and the electrolyte's wettability to the positive electrode sheet, thereby increasing the lithium ion transmission rate. The amine group and the silane group can increase the adhesion of the three-dimensional network skeleton to the positive electrode active material. At the same time, controlling the ratio of the number of amine groups and / or silane groups to the number of ester groups can achieve a better fit between the flexibility of the positive electrode sheet, the wettability of the electrolyte to the positive electrode sheet, and the adhesion of the three-dimensional network skeleton to the positive electrode active material, thereby improving the battery's safety performance and cycle performance and reducing the battery's expansion rate.

[0009] Other features and advantages of the present invention will be described in detail in the following detailed description.

[0010] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Shown is a schematic structural diagram of the positive electrode sheet of the present invention. DETAILED DESCRIPTION

[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.

[0013] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.

[0014] A first aspect of the present invention provides a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, the positive electrode active material layer comprises a three-dimensional network skeleton and a positive electrode active material located in the three-dimensional network skeleton, the three-dimensional network skeleton is formed by a conductive adhesive, the conductive adhesive comprises carbon nanotubes and a bonding layer located on at least a portion of the surface of the carbon nanotubes, the bonding layer comprises an ester group, an amine group and a silane group, wherein the ratio of the number of the amine groups and / or the silane groups to the number of the ester groups is (3-6):1.

[0015] like Figure 1 As shown, the positive electrode sheet includes a positive electrode current collector 01 and a positive electrode active material layer located on one side or both sides of the positive electrode current collector 01, the positive electrode active material layer includes a three-dimensional network skeleton and a positive electrode active material 02 located in the three-dimensional network skeleton, the three-dimensional network skeleton is formed by a conductive adhesive 03, and the conductive adhesive 03 includes carbon nanotubes and a bonding layer located on at least part of the surface of the carbon nanotubes. The bonding layer is connected to the carbon nanotubes through specific functional groups (such as ester groups, amine groups and silane groups). The connection can be achieved by modifying the surface of the carbon nanotubes. Therefore, there is a connecting force between the bonding layer and the carbon nanotubes, and the bonding layer is not simply attached to the surface of the carbon nanotubes.

[0016] It is understandable that the bonding layer may be located on the entire surface of the carbon nanotube or on a portion of the surface of the carbon nanotube. Whether the bonding layer is located on a portion of the surface of the carbon nanotube or on the entire surface of the carbon nanotube, the bonding agent has little or no effect on the conductivity of the carbon nanotube, so the carbon nanotube still has conductivity and can meet the conductivity requirements of the positive electrode sheet.

[0017] In the present invention, the conductive binder comprises carbon nanotubes and a bonding layer located on the surface of the carbon nanotubes, the positive electrode active material is located in a three-dimensional network skeleton formed by the conductive binder, and the three-dimensional network skeleton is formed by the conductive binder, wherein both ends of the carbon nanotubes in the three-dimensional network skeleton can be uniformly embedded in the positive electrode sheet, forming a three-dimensional conductive network in the positive electrode active material layer, thereby improving the electron conduction capacity of the positive electrode sheet, reducing the transmission resistance of the electrons, and improving the cycle performance of the battery, and the bonding layer in the three-dimensional network skeleton can improve the bonding property of the conductive binder, thereby improving the three-dimensional network skeleton to the positive electrode. The bonding layer comprises functional groups of ester, amine and silane, wherein the ester group can improve the infiltration of the electrolyte into the bonding layer on the surface of the carbon tube, making the bonding layer flexible and improving the flexibility of the three-dimensional network skeleton, thereby improving the flexibility of the positive electrode sheet and the safety performance of the battery, and the ester group in the bonding layer can also improve the wettability of the electrolyte to the positive electrode sheet, improve the transmission rate of lithium ions, and reduce the diffusion resistance of lithium ions in the solid electrolyte interface; the amine and silane groups can improve the adhesion of the three-dimensional network skeleton, thereby improving the adhesion of the three-dimensional network skeleton to the positive electrode active material. Relay, and at the same time, by controlling the ratio of the number of the amine groups and / or the silane groups to the number of the ester groups to be (3-6):1 (for example, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1), the flexibility of the positive electrode sheet, the wettability of the electrolyte to the positive electrode sheet, and the adhesion of the three-dimensional network skeleton to the positive electrode active material can achieve better adaptability, avoiding excessive adhesion of the three-dimensional network skeleton to the positive electrode active material due to excessive number of amine groups and / or silane groups, resulting in too small a gap in the positive electrode active material layer, and the wettability of the electrolyte to the positive electrode active material layer. The transmission of lithium ions is reduced, thus hindering the transmission of lithium ions. In addition, the adhesion of the three-dimensional network skeleton to the positive electrode active material is too strong, which will also lead to excessive electron flow on the surface of the positive electrode active material, which is not matched with the lithium ion flow on the surface of the positive electrode active material, resulting in a decrease in the rate of lithium removal and lithium insertion of the positive electrode active material, thereby reducing the cycle performance and safety performance of the battery. It also avoids the excessive wettability of the electrolyte to the positive electrode sheet due to too many ester groups, resulting in excessive swelling of the bonding layer in the conductive adhesive, reducing the adhesion of the three-dimensional network skeleton to the positive electrode active material, increasing the expansion rate of the battery, and reducing the safety performance of the battery.

[0018] In the present invention, by providing a three-dimensional network skeleton in the positive electrode active material layer and controlling the ratio of the number of amine groups and / or silane groups to the number of ester groups in the binding layer of the three-dimensional network skeleton, the cycle performance and safety performance of the battery can be improved and the cycle expansion rate of the battery can be reduced compared with the prior art. In order to further improve the effect, one or more of the technical features can be further optimized.

[0019] In one example, the bonding layer is located on a portion of the surface of the carbon nanotube.

[0020] In one example, the ratio of the number of the amine groups and / or the silane groups to the number of the ester groups is (4-5):1 (e.g., 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1 or 5:1).

[0021] In the present invention, the number of the amine groups, silane groups and ester groups can be tested by the following method: directly characterize the conductive adhesive by infrared spectrometer to obtain an infrared spectrum curve, and then calculate the number of the amine groups, silane groups and ester groups according to the Lambert-Beer law.

[0022] In one example, the bonding layer further includes one or more of the following functional groups: methyl, carboxyl, and hydroxyl. Among them, the methyl group can improve the flexibility of the three-dimensional network skeleton, thereby improving the flexibility of the positive electrode sheet, avoiding the fracture of the electrode sheet, and improving the safety performance of the battery; the carboxyl and hydroxyl groups can improve the adhesion of the three-dimensional network skeleton and enhance the adhesion of the three-dimensional network skeleton to the positive electrode active material, thereby improving the cycle performance of the battery and reducing the expansion rate of the battery.

[0023] In one example, the bonding layer includes an ester group, an amine group, and a silane group and one or more of the following functional groups: a methyl group, a carboxyl group, and a hydroxyl group.

[0024] In one example, the conductive adhesive has an aspect ratio of ≥10 (eg, 10, 50, 100, 300, 500, 800, 1000, 1500, 2000, 2500, 3000, 4000, 5000, 6000, or 7000).

[0025] In one example, the conductive adhesive has an aspect ratio of ≥1000.

[0026] According to a specific embodiment, the bonding layer includes an ester group, an amine group and a silane group and one or more of the following functional groups: a methyl group, a carboxyl group, and a hydroxyl group, and the aspect ratio of the conductive adhesive is ≥ 1000. By controlling the aspect ratio of the conductive adhesive within the above range and controlling the functional groups in the bonding layer, both ends of the carbon nanotubes with a larger aspect ratio can be uniformly embedded in the positive electrode sheet, and at the same time, in coordination with the bonding layer having the above specific functional groups, the flexibility of the positive electrode sheet can be further improved while improving the electron transport kinetics of the positive electrode sheet, thereby avoiding deformation of the positive electrode sheet when squeezed, which increases safety risks.

[0027] In one example, the conductive adhesive has an aspect ratio of ≥1500.

[0028] In one example, the conductive adhesive has an aspect ratio of ≥2000.

[0029] In one example, the conductive adhesive has an aspect ratio of ≥5000.

[0030] In the present invention, the aspect ratio of the conductive adhesive is the ratio of the average length of the conductive adhesive to the average tube diameter.

[0031] In one example, the conductive adhesive has an average tube diameter of 2 nm to 10 nm (e.g., 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, or 10 nm).

[0032] In the present invention, the average tube diameter of the conductive adhesive can be obtained by testing in the following way: directly photographing the morphology of the conductive adhesive by transmission electron microscopy (TEM), and measuring the outer diameters of at least 20 characterized conductive adhesives, and then obtaining the average tube diameter of the conductive adhesive.

[0033] In one example, the conductive adhesive has an average length of 13 μm to 17 μm (eg, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm, 16.5 μm, or 17 μm).

[0034] In the present invention, the average length of the conductive adhesive can be tested by the following method: directly photographing the morphology of the conductive adhesive by scanning electron microscopy (SEM), and measuring the lengths of at least 20 characterized conductive adhesives, and then obtaining the average length of the conductive adhesive.

[0035] According to a specific implementation, the average tube diameter of the conductive adhesive is 6 nm-10 nm, the average length of the conductive adhesive is 13 μm-17 μm, and the aspect ratio of the conductive adhesive is ≥1000.

[0036] In one example, the thickness of the tube wall of the conductive adhesive is 6 nm-7 nm (eg, 6 nm, 6.1 nm, 6.2 nm, 6.3 nm, 6.4 nm, 6.5 nm, 6.6 nm, 6.7 nm, 6.8 nm, 6.9 nm, or 7 nm).

[0037] In the present invention, the thickness of the tube wall of the conductive adhesive can be tested by the following method: directly photographing the morphology of the conductive adhesive through a transmission electron microscope (TEM), and measuring the thickness of the tube wall of at least 20 characterized conductive adhesives (the difference between the outer diameter and the hollow inner diameter), and then calculating the average value to obtain the thickness of the tube wall of the conductive adhesive.

[0038] In one example, the weight proportion of the carbon nanotubes with a length > 8 μm in all carbon nanotubes is ≥ 50% (e.g., 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%).

[0039] In one example, the weight proportion of the carbon nanotubes with a length of more than 8 μm in all carbon nanotubes is 70%-90%. By controlling the weight proportion of the carbon nanotubes with a length of more than 8 μm in all carbon nanotubes within the above range, it is possible to achieve the combination of carbon nanotubes with a length of more than 8 μm (long-range conductive agent) and carbon nanotubes with a length of ≤ 8 μm (short-range conductive agent), improve the integrity of the conductive network formed by the carbon nanotubes, avoid interruptions in the electron transmission process, make the electron conduction performance of the positive electrode active material layer smoother, and further improve the cycle stability of the battery.

[0040] In the present invention, the terms "length" and "average length" have different meanings. The term "length" refers to the length of a single carbon nanotube. For example, a carbon nanotube with a length > 8 μm means a carbon nanotube with a length > 8 μm of a single carbon nanotube; the weight proportion of the carbon nanotube with a length > 8 μm in all carbon nanotubes means the ratio of the sum of the weights of the carbon nanotubes with a length > 8 μm of a single carbon nanotube to the sum of the weights of all carbon nanotubes. The term "average length" refers to the average value of the lengths of all conductive binders in a system. For example, the average length of a conductive binder means the average value of the lengths of all conductive binders in a system.

[0041] In one example, the ratio of the thickness of the adhesive layer to the diameter of the conductive adhesive is 0.1-0.4 (for example, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35 or 0.4). By controlling the ratio of the thickness of the adhesive layer to the diameter of the conductive adhesive within the above range, the bonding force of the conductive adhesive can be maximized without sacrificing the conductivity of the conductive adhesive. When the ratio of the thickness of the adhesive layer to the diameter of the conductive adhesive is lower than 0.1, the degree of modification of the conductive adhesive is low, resulting in weak bonding force of the conductive adhesive. When the ratio of the thickness of the adhesive layer to the diameter of the conductive adhesive is higher than 0.4, since the adhesive layer is a non-conductive material, although the bonding force is strong, the electronic conductivity is weakened.

[0042] In one example, the ratio of the thickness of the adhesive layer to the tube diameter of the conductive adhesive is 0.15-0.25.

[0043] In the present invention, the term "tube diameter" and "average tube diameter" have different meanings. The term "tube diameter" refers to the outer diameter of a single conductive adhesive. The term "average tube diameter" refers to the average value of the outer diameters of all conductive adhesives in a system.

[0044] According to a specific embodiment, the average tube diameter of the conductive adhesive is 2nm-10nm, the average length of the conductive adhesive is 13μm-17μm, the aspect ratio of the conductive adhesive is ≥1000, the thickness of the tube wall of the conductive adhesive is 6nm-7nm, the weight proportion of the carbon nanotubes with a length of >8μm in all carbon nanotubes is 70%-90%, and the ratio of the thickness of the bonding layer to the tube diameter of the conductive adhesive is 0.15-0.25.

[0045] In one example, the degree of crosslinking between the conductive binder and the positive electrode active material is ≥ 0.1. Controlling the degree of crosslinking between the conductive binder and the positive electrode active material within the above range can increase the bonding force between the conductive binder and the positive electrode active material, shorten the distance between the positive electrode active material and the carbon nanotubes in the conductive binder, shorten the electron transmission distance, and can also increase the rate of lithium insertion and removal of the positive electrode active material by improving electron conduction, improve the structural stability of the positive electrode active material, and thus improve the cycle stability of the battery. When the degree of crosslinking between the conductive binder and the positive electrode active material is less than 0.1, the bonding force between the conductive binder and the positive electrode active material is low, the distance between the positive electrode active material and the conductive binder is large, and the electron transmission distance is long, which affects the cycle stability of the battery.

[0046] In one example, the degree of crosslinking between the conductive binder and the positive active material is 0.1-3 (eg, 0.1, 0.2, 0.3, 0.4, 0.5, 0.8, 1, 1.3, 1.5, 1.8, 2, 2.3, 2.5, 2.8, or 3).

[0047] In one example, the crosslinking degree between the conductive binder and the positive electrode active material is 0.15-0.5.

[0048] In the present invention, the degree of crosslinking between the conductive binder and the positive electrode active material represents the average number of conductive binders in contact with the surface of a single positive electrode active material particle. It is understood that the degree of crosslinking between the conductive binder and the positive electrode active material is a dimensionless constant, which can be obtained by testing in the following way: within an area of ​​100 μm*100 μm on the surface of the positive electrode sheet, 50 particles of positive electrode active material are randomly selected, and the number of conductive binders in contact with the surface of each positive electrode active material particle is calculated, and the degree of crosslinking between the conductive binder and the positive electrode active material = (the sum of the number of conductive binders in contact with the surfaces of 50 positive electrode active material particles) / 50.

[0049] like Figure 1As shown, the positive electrode active material layer may further include carbon black 04. Carbon black has electrical conductivity, which can further improve the electronic conductivity of the positive electrode active material layer, increase the electron transfer rate in the positive electrode active material layer, and accelerate the charge transfer kinetics of the positive electrode active material layer, thereby improving the cycle performance of the battery.

[0050] In one example, the carbon black includes one or more of furnace black, acetylene black and Ketjen black.

[0051] In one example, the specific surface area of ​​the carbon black is 30 m 2 / g-150m 2 / g (for example, 30m 2 / g, 50m 2 / g, 80m 2 / g、100m 2 / g, 130m 2 / g or 150m 2 / g). Controlling the specific surface area of ​​the carbon black within the above range can make the carbon black have higher conductivity and better dispersibility and less prone to agglomeration. When the specific surface area of ​​the carbon black is less than 30m 2 / g, the conductivity is low, and the conductivity improvement effect on the positive electrode active material layer is limited; when the specific surface area of ​​the carbon black is higher than 150m 2 / g, the dispersion of carbon black is poor, and it will also react with the electrolyte, affecting the cycle performance of the battery.

[0052] In one embodiment, the specific surface area of ​​the carbon black is 50 m 2 / g-80m 2 / g.

[0053] In one example, the oil absorption value of the carbon black is ≥300ml / 100g (for example, 300ml / 100g, 350ml / 100g, 400ml / 100g, 500ml / 100g, 600ml / 100g, 700ml / 100g, 800ml / 100g, 900ml / 100g, 1000ml / 100g or 1500ml / 100g). Controlling the oil absorption value of the carbon black to be ≥300ml / 100g can improve the liquid retention of the battery cell together with the conductive binder, improve the transmission rate of lithium ions, and improve the cycle stability of the battery. When the oil absorption value of the carbon black is <300ml / 100g, the liquid retention of the battery cell is low, and it will also affect the cycle performance of the battery.

[0054] In one example, the carbon black has an oil absorption value of 320 ml / 100 g to 360 ml / 100 g.

[0055] In one example, the weight percentage X of carbon black in the positive electrode active material layer is 0.2%-1% (eg, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%).

[0056] In one example, the weight percentage X of carbon black in the positive electrode active material layer is 0.3%-0.6%.

[0057] In one example, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0058] In one example, the carbon nanotubes include single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0059] In one example, the weight proportion Y of the multi-walled carbon nanotubes in the positive electrode active material layer is 0.3%-0.8% (for example, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75% or 0.8%).

[0060] In one example, the weight ratio Y of the multi-walled carbon nanotubes in the positive electrode active material layer is 0.4%-0.6%.

[0061] In one example, the aspect ratio W of the multi-walled carbon nanotubes is 1000-10000 (eg, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000 or 10000).

[0062] In one example, the aspect ratio W of the multi-walled carbon nanotubes is 2000-5000.

[0063] In the present invention, the aspect ratio of the multi-walled carbon nanotubes is the ratio of the average length of the multi-walled carbon nanotubes to the average tube diameter of the multi-walled carbon nanotubes, wherein the average tube diameter is the average value of the outer diameters of the multi-walled carbon nanotubes.

[0064] In one example, the weight percentage Z of the single-walled carbon nanotubes in the positive electrode active material layer is 0.05%-0.5% (for example, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%).

[0065] In one example, the weight percentage Z of the single-walled carbon nanotubes in the positive electrode active material layer is 0.1%-0.3%.

[0066] In one example, the positive electrode sheet satisfies the following relationship: 0.25%≤Z+Y≤2.5% (for example, 0.25%, 0.5%, 1%, 1.5%, 2% or 2.5%), and / or, 2≤Y / Z≤5 (for example, 2, 2.5, 3, 3.5, 4, 4.5 or 5), and / or, X=0.82 / (Y×W / 1000), wherein X is the weight percentage of carbon black in the positive electrode active material layer, in %, Y is the weight percentage of multi-walled carbon nanotubes in the positive electrode active material layer, in %, Z is the weight percentage of single-walled carbon nanotubes in the positive electrode active material layer, in %, and W is the aspect ratio of multi-walled carbon nanotubes.

[0067] Controlling the positive electrode sheet so that it satisfies the above-mentioned relationship can achieve better adaptation of single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon black, thereby further improving the conductivity of the positive electrode active material layer. For example, when the weight proportion of multi-walled carbon nanotubes in the positive electrode active material layer is certain, if the aspect ratio of the multi-walled carbon nanotubes is relatively small and / or the weight proportion of single-walled carbon nanotubes in the positive electrode active material layer is low, the conductivity of the positive electrode active material layer can be improved by increasing the weight proportion of carbon black in the positive electrode active material layer. If the aspect ratio of the multi-walled carbon nanotubes is relatively large and / or the weight proportion of single-walled carbon nanotubes in the positive electrode active material layer is relatively large, the weight proportion of carbon black in the positive electrode active material can be reduced without having a significant impact on the conductivity of the positive electrode active layer. In addition, through the coordination of single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon black, the structural stability of the positive electrode active material layer can be further improved, and the wettability of the electrolyte to the positive electrode active material layer can be improved, so that the electron flow and lithium ion flow on the surface of the positive electrode active material can be better matched, avoiding the volume change of the positive electrode active material, thereby improving the cycle stability of the battery and reducing the expansion rate of the battery.

[0068] In one example, 0.5%≤Z+Y≤1.3%.

[0069] According to a specific embodiment, the weight proportion X of carbon black in the positive electrode active material layer is 0.3%-0.6%, the weight proportion Y of multi-walled carbon nanotubes in the positive electrode active material layer is 0.4%-0.6%, the aspect ratio W of the multi-walled carbon nanotubes is 2000-5000, the weight proportion Z of single-walled carbon nanotubes in the positive electrode active material layer is 0.1%-0.3%, and the positive electrode sheet satisfies the following relationship: 0.25%≤Z+Y≤2.5%, and 2≤Y / Z≤5, and X=0.82 / (Y×W / 1000).

[0070] In one example, the positive electrode active material layer also contains a first modifier and a polymer additive. The first modifier can be attached around the three-dimensional network skeleton to improve the cohesion of the positive electrode active material layer, further improve the flexibility of the positive electrode sheet and the adhesion between the positive electrode current collector and the positive electrode active material layer, and improve the cycle performance and safety performance of the battery. The polymer additive can be evenly dispersed in the positive electrode active material layer, thereby further improving the cohesion of the positive electrode active layer, improving the adhesion between the positive electrode current collector and the positive electrode active material layer, reducing the cycle expansion rate of the battery, and improving the cycle performance of the battery.

[0071] In one example, the first modifier includes one or more of hexadecyltrimethylammonium tetrafluoroborate, N-(cocoalkyl)-N,N,N-trimethylammonium methyl sulfate, cocamidopropyl betaine hexadecyltrimethylammonium acetate, and hexadecyltrimethylammonium nitrate.

[0072] In one example, the polymer additive includes one or more of polyamide, modified polyamide, and polyamide derivatives.

[0073] In one example, the molecular weight of the polymer additive is 1,000,000 g / mol-2,000,000 g / mol (e.g., 1,000,000 g / mol, 1,200,000 g / mol, 1,400,000 g / mol, 1,500,000 g / mol, 1,700,000 g / mol, 1,900,000 g / mol, or 2,000,000 g / mol).

[0074] In one example, the molecular weight of the polymer additive is 1,200,000 g / mol-1,500,000 g / mol.

[0075] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 96%-98.7% (for example, 96%, 96.5%, 97%, 97.5%, 98%, 98.5% or 98.7%), the weight content of the conductive binder is 0.4%-0.9% (for example, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or 0.9%), the weight content of the first modifier is 0.25-1.5% (for example, 0.25%, 0.5%, 0.75%, 1%, 1.25% or 1.5%), and the weight content of the polymer additive is <1% (for example, 0.9%, 0.7%, 0.5%, 0.3%, 0.1%).

[0076] In one example, the positive electrode active material includes a lithium cobalt oxide material.

[0077] In one example, the lithium cobalt oxide material includes a doping element, and the doping element includes one or more of Mg, Zr, La, Al, and Nb.

[0078] In one example, based on the total weight of the lithium cobalt oxide material, the weight content of element Al is 0.05%-1% (eg, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8% or 1%).

[0079] In one example, based on the total weight of the lithium cobalt oxide material, the weight content of element Mg is 0.05%-0.5% (eg, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%).

[0080] In one example, based on the total weight of the lithium cobalt oxide material, the weight content of the element Zr is 0.05%-0.5% (eg, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%).

[0081] In one example, based on the total weight of the lithium cobalt oxide material, the weight content of element La is 0.05%-0.5% (eg, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%).

[0082] In one example, based on the total weight of the lithium cobalt oxide material, the weight content of the element Nb is 0.05%-0.5% (eg, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%).

[0083] In one example, the median particle size Dv50 of the lithium cobalt oxide is 8 μm-15 μm (eg, 8 μm, 9 μm, 10 μm, 1 μm, 12 μm, 13 μm, 14 μm, or 15 μm).

[0084] In one example, the bonding layer in the conductive adhesive is formed by modifying carbon nanotubes with a second modifier, and the functional groups in the bonding layer are provided by the second modifier.

[0085] In one example, the second modifier includes one or more of diethyl adipate, diethyl dimethylmalonate, diethyl suberate, dimethyl malonate, dimethyl suberate, methyl valerate, propyl butyrate, n-dodecyltrimethoxysilane, silane coupling agent, trimethylsilane, hexadecyltrimethylammonium tetrafluoroborate, N-(coconut alkyl)-N,N,N-trimethyl methylammonium sulfate, cocamidopropyl betaine, hexadecyltrimethylammonium acetate and hexadecyltrimethylammonium nitrate.

[0086] In one example, the porosity of the positive electrode sheet is 20%-35% (e.g., 20%, 23%, 25%, 28%, 30%, 33% or 35%). Controlling the porosity of the positive electrode sheet within the above range can improve the porosity of the positive electrode sheet, thereby further improving the wettability of the electrolyte to the positive electrode sheet, increasing the transmission rate of the lithium-ion battery, reducing the diffusion resistance of lithium ions, improving the problem of lithium plating and / or purple spots in the battery, and improving the cycle performance and safety performance of the battery.

[0087] In one example, the peeling force between the positive electrode current collector and the positive electrode active material layer is ≥30 N / m.

[0088] In the present invention, the peeling force between the positive electrode current collector and the positive electrode active material layer can be tested by the following method: the electrode sheet is cut into 24 mm width and 30 cm length, a certain specification of tape is used, and a tensile testing machine is used to test the peeling force of the electrode sheet, and then the obtained peeling force is divided by the electrode sheet width to obtain the electrode sheet peeling strength.

[0089] In one example, the surface density of the positive electrode sheet is 25 mg / cm 2 -35mg / cm 2 (e.g., 25 mg / cm 2 , 26mg / cm 2 , 27mg / cm 2 、28mg / cm 2 , 29mg / cm 2 、30mg / cm 2 、31mg / cm 2 、32mg / cm 2 、33mg / cm 2 、34mg / cm 2 or 35mg / cm 2 ). In the present invention, the surface density refers to the single-sided surface density, and the surface density of the positive electrode sheet means that when there is a positive electrode active material layer on one side of the positive electrode current collector, the surface density of the positive electrode sheet is the surface density of this side (i.e., the side with the positive electrode active material layer); when there are positive electrode active material layers on both sides of the positive electrode current collector, the densities of the two sides of the positive electrode sheet are the same, and the surface density of the positive electrode sheet is the surface density of either side.

[0090] A second aspect of the present invention provides a battery, which includes the positive electrode sheet described in the first aspect of the present invention.

[0091] The materials of the battery except the positive electrode sheet can be made according to the methods in the art, and can achieve lower cycle thickness expansion rate, higher cycle performance and higher safety performance.

[0092] In one example, the battery is a lithium-ion battery.

[0093] In one example, the battery further includes an electrolyte, a negative electrode sheet, and a separator.

[0094] In one example, the electrolyte includes a carbonate solvent, the carbonate solvent includes an ester group, and the bonding layer of the conductive adhesive forming the three-dimensional network skeleton of the positive electrode sheet includes an ester group. According to the principle of like dissolves like, the electrolyte has a high wettability to the positive electrode sheet.

[0095] In one example, the carbonate solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC) and dimethyl carbonate (DMC).

[0096] In one example, the electrolyte further includes a lithium salt and an additive.

[0097] In one embodiment, the lithium salt includes lithium hexafluorophosphate (LiPF 6 ), lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), and lithium tetrafluoroborate (LiBF 4 )

[0098] In one example, the additive includes one or more of fluoroethylene carbonate (FEC), vinylene carbonate (VC), 1,3-propane sultone (PS), 1,3-acrylonitrile lactone (PST), vinyl ethylene carbonate (VEC), succinonitrile (SN) and 1,3,6-hexanetrinitrile (HTCN).

[0099] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 10%-40% (for example, 10%, 15%, 20%, 25%, 30%, 35% or 40%), the weight content of the carbonate solvent is 40%-80% (for example, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%), and the weight content of the additive is 3%-20% (3%, 5%, 10%, 15% or 20%).

[0100] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 12%-35%, the weight content of the carbonate solvent is 50%-70%, and the weight content of the additive is 5%-15%.

[0101] In one example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material, a negative electrode conductor, a negative electrode binder and a thickener.

[0102] In one example, the negative electrode active material includes one or more of a graphite negative electrode material, a silicon negative electrode material, a silicon-oxygen negative electrode material, a silicon-carbon negative electrode material, and a soft carbon negative electrode material.

[0103] In one example, the negative electrode conductive agent includes one or more of furnace black, acetylene black, Ketjen black and carbon nanotubes.

[0104] In one example, the negative electrode binder includes one or more of styrene-butadiene rubber (SBR) and polyacrylic acid (PAA).

[0105] In one example, the thickener includes one or more of carboxymethyl cellulose lithium (CMC-li), polyacrylic acid (PAA) and polyacrylonitrile (PAN).

[0106] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 85%-98% (for example, 85%, 88%, 90%, 93%, 95% or 98%), the weight content of the negative electrode conductor is 0.1%-10% (for example, 0.1%, 0.5%, 1%, 3%, 5%, 8% or 10%), the weight content of the negative electrode binder is 0.1-10% (for example, 0.1%, 0.5%, 1%, 3%, 5%, 8% or 10%), and the weight content of the thickener is 0.1%-10% (for example, 0.1%, 0.5%, 1%, 3%, 5%, 8% or 10%).

[0107] In one example, the diaphragm includes a substrate, a ceramic layer located on one side or both sides of the substrate, and a coating layer located on the surface of the substrate and / or the surface of the ceramic.

[0108] In one example, the substrate includes one or more of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyparaphenylene, polynaphthalene, polyimide, polyamide, aramid, and polyparaphenylenebenzodithiazole.

[0109] In one example, the ceramic layer includes inorganic particles and a separator binder.

[0110] In one example, the inorganic particles include one or more of aluminum oxide, boehmite, silicon dioxide, zirconium dioxide, barium sulfate, magnesium hydroxide, fluoroapatite, fluorophlogopite, mullite, aluminum titanate, copper oxide, titanium dioxide, and zinc oxide.

[0111] In one example, the separator binder includes one or more of polytetrafluoroethylene (PVDF) and polymethyl methacrylate (PMMA).

[0112] In one example, based on the total weight of the ceramic layer, the weight content of the inorganic particles is 50%-60% (e.g., 50%, 53%, 55%, 58% or 60%), and the weight content of the diaphragm binder is 40%-50% (e.g., 40%, 43%, 45%, 48% or 50%).

[0113] In one example, the thickness of the ceramic layer is 0.5 μm-3 μm (eg, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, or 3 μm).

[0114] In one example, the coating layer includes one or more of polytetrafluoroethylene (PVDF) and polymethyl methacrylate (PMMA).

[0115] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0116] The following is used to illustrate the positive electrode sheet and battery of the present invention.

[0117] Example 1

[0118] (1) Positive electrode

[0119] The positive electrode active material (lithium cobalt oxide material (Dv50 particle size is 11.95 μm), the weight content of Al element in the lithium cobalt oxide material is 0.65%, the weight content of Mg element is 0.25%, the weight content of Zr element is 0.15%, the weight content of La element is 0.25%, and the weight content of Nb element is 0.15%), carbon black (acetylene black), conductive binder (wherein the carbon nanotubes include multi-walled carbon nanotubes and single-walled carbon nanotubes, and the second modifier is hexadecyl trimethylammonium acetate and propyl butyrate), a first modifier (hexadecyltrimethylammonium nitrate) and a polymer additive (polyamide) were fully mixed in a mass ratio of 97.35:0.35:0.8:1:0.5, and N-methylpyrrolidone was added, and then fully stirred and vacuum defoamed to form a uniform positive electrode slurry. The positive electrode slurry was coated on both sides of a positive electrode current collector (aluminum foil) with a thickness of 9 μm to form a positive electrode active material layer. The surface density of the positive electrode sheet was 28.25 mg / cm 2 Then it is dried in an oven at 110-135℃ and rolled (the compaction density is 4.0g / cm 3 ), cut to obtain the positive electrode sheet.

[0120] (2) Negative electrode

[0121] The negative electrode active material (artificial graphite), negative electrode conductive agent (carbon black), negative electrode binder (styrene-butadiene rubber), and thickener (sodium carboxymethyl cellulose) were fully mixed in a mass ratio of 96.7:0.7:1.3:1.3, and deionized water was added. Then, the mixture was fully stirred and vacuum-defoamed to form a uniform negative electrode slurry. The negative electrode slurry was coated on both sides of the negative electrode current collector (copper foil) with a thickness of 6 μm to form a negative electrode active material layer. The coating surface density was 15.29 mg / cm 2 Then it was dried in an oven at 80℃ and rolled (the compaction density was 1.7g / cm 3 ), cut to obtain the negative electrode sheet.

[0122] (3) Electrolyte

[0123] In a glove box filled with argon (H 2 O<0.05ppm,O 2 <0.05ppm), carbonate solvents (EC, PC, DMC mass ratio of 1:1:1, a total of 65 parts by weight) were mixed evenly to obtain an electrolyte solvent, and then 14% of lithium hexafluorophosphate (LiPF 6 ) and 6% LiTFSI, and then continue to add 15% additives based on the total mass of the electrolyte after dissolution (wherein the additives include FEC, PS, 1,3,6-hexanetricarbonitrile (HTCN), and the weight ratio of FEC:PS:HTCN is 7:3:5), stir evenly, and obtain the electrolyte after passing the moisture and free acid tests.

[0124] (4) Diaphragm

[0125] Weigh inorganic particles (aluminum oxide) with a Dv50 particle size of 0.5 μm and a diaphragm binder (PVDF), disperse them in N-methylpyrrolidone at a mass ratio of 55:45, stir them thoroughly to form a ceramic coating slurry, and use a gravure coating process to coat the ceramic coating slurry on one side of a PE diaphragm substrate (the thickness of the substrate is 7 μm) to form a ceramic layer. The thickness of the ceramic coating is 1.5 μm. Dissolve PVDF in N-methylpyrrolidone to form a coating layer slurry, and coat the coating layer slurry on the other side of the substrate layer to form a coating layer. After drying, a diaphragm is obtained.

[0126] (5) Lithium-ion battery

[0127] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are stacked in order, so that the separator is located between the positive electrode sheet and the negative electrode sheet, and the ceramic coating in the separator faces the positive electrode sheet, and then the bare battery cell is obtained by welding the tabs and winding, and the bare battery cell is placed in a 0.09 mm aluminum-plastic film shell, and a lithium-ion battery is prepared through packaging, liquid injection (the electrolyte prepared in step (3) is injected into the aluminum-plastic film shell), formation, secondary sealing, sorting and other processes. See Table 1-1, Table 1-2 and Table 1-3 for details.

[0128] Example 2

[0129] (1) Positive electrode

[0130] The positive electrode active material (lithium cobalt oxide material (Dv50 particle size is 8.2 μm), the weight content of Al element in the lithium cobalt oxide material is 0.75%, the weight content of Mg element is 0.35%, the weight content of Zr element is 0.15%, the weight content of La element is 0.35%, and the weight content of Nb element is 0.15%), carbon black (Ketjen black), conductive binder (wherein carbon nanotubes include multi-walled carbon nanotubes and single-walled carbon nanotubes, and the second modifier is cocoamidopropyl Betaine and diethyl adipate), a first modifier (cocamidopropyl betaine) and a polymer additive (polyamide) are fully mixed in a mass ratio of 96.2:0.13:1.5:1.2:0.97, and N-methylpyrrolidone is added, and then fully stirred and vacuum defoamed to form a uniform positive electrode slurry. The positive electrode slurry is coated on both sides of a positive electrode current collector (aluminum foil) with a thickness of 9 μm to form a positive electrode active material layer. The surface density of the positive electrode sheet is 28.25 mg / cm 2 Then it is dried in an oven at 110-135℃ and rolled (the compaction density is 4.0g / cm 3 ), cut to obtain the positive electrode sheet.

[0131] (2) The negative electrode sheet was prepared in accordance with Example 1.

[0132] (3) Electrolyte

[0133] In a glove box filled with argon (H 2 O<0.05ppm,O 2 <0.05ppm), a carbonate solvent (EC, PC, DMC mass ratio of 1:1:1, a total of 55 parts by weight) was mixed evenly to obtain an electrolyte solvent, and then 14% of lithium hexafluorophosphate (LiPF 6) and 6% LiTFSI, and then continue to add 25% additives based on the total mass of the electrolyte after dissolution (wherein the additives include FEC, PS, 1,3,6-hexanetricarbonitrile (HTCN), and the weight ratio of FEC:PS:HTCN is 7:3:5), stir evenly, and obtain the electrolyte after passing the moisture and free acid tests.

[0134] (4) The diaphragm was prepared in accordance with Example 1.

[0135] (5) Lithium-ion battery is prepared in accordance with Example 1. For details, see Table 1-1, Table 1-2 and Table 1-3.

[0136] Example 3

[0137] (1) Positive electrode

[0138] The positive electrode active material (lithium cobalt oxide material (Dv50 particle size is 14.5 μm), the weight content of Al element in the lithium cobalt oxide material is 0.45%, the weight content of Mg element is 0.05%, the weight content of Zr element is 0.25%, the weight content of La element is 0.15%, and the weight content of Nb element is 0.15%), carbon black (furnace carbon black), conductive binder (wherein the carbon nanotubes include multi-walled carbon nanotubes and single-walled carbon nanotubes, and the second modifier is hexadecyl tris(III)) is prepared by mixing with the following mixture: Methyl ammonium nitrate and methyl valerate), a first modifier (hexadecyl trimethyl ammonium nitrate) and a polymer additive (polyamide) are fully mixed in a mass ratio of 9792:0.32:1.1:0.26:0.4, and N-methyl pyrrolidone is added, and then fully stirred and vacuum defoamed to form a uniform positive electrode slurry. The positive electrode slurry is coated on both sides of a positive electrode current collector (aluminum foil) with a thickness of 9 μm to form a positive electrode active material layer. The surface density of the positive electrode sheet is 28.25 mg / cm 2 Then it is dried in an oven at 110-135℃ and rolled (the compaction density is 4.0g / cm 3 ), cut to obtain the positive electrode sheet.

[0139] (2) The negative electrode sheet was prepared in accordance with Example 1.

[0140] (3) Electrolyte

[0141] In a glove box filled with argon (H 2 O<0.05ppm,O 2 <0.05ppm), a carbonate solvent (EC, PC, DMC mass ratio of 1:1:1, a total of 75 parts by weight) was mixed evenly to obtain an electrolyte solvent, and then 14% of lithium hexafluorophosphate (LiPF 6) and 6% LiTFSI, and then continue to add 5% additives based on the total mass of the electrolyte after dissolution (wherein the additives include FEC, PS, 1,3,6-hexanetricarbonitrile (HTCN), and the weight ratio of FEC:PS:HTCN is 7:3:5), stir evenly, and obtain the electrolyte after passing the moisture and free acid tests.

[0142] (4) The diaphragm was prepared in accordance with Example 1.

[0143] (5) Lithium-ion battery is prepared in accordance with Example 1. For details, see Table 1-1, Table 1-2 and Table 1-3.

[0144] Example 4 Group

[0145] This group of examples is used to illustrate the effects produced when the ratio of the number of amine groups and / or silane groups to the number of ester groups is changed.

[0146] This example group was carried out with reference to Example 1, except that the ratio of the number of amine groups and / or silane groups to the number of ester groups was changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.

[0147] Example 5 Group

[0148] This group of embodiments is used to illustrate the effects produced when the aspect ratio of the conductive adhesive is changed.

[0149] This embodiment group is carried out with reference to the embodiment 1, except that the aspect ratio of the conductive adhesive is changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.

[0150] Example 6 Group

[0151] This group of embodiments is used to illustrate the impact when the ratio of the thickness of the adhesive layer to the tube diameter of the conductive adhesive changes.

[0152] This embodiment group is carried out with reference to the embodiment 1, except that the ratio of the thickness of the adhesive layer to the tube diameter of the conductive adhesive is changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.

[0153] Example 7 Group

[0154] This group of examples is used to illustrate the effects produced when the degree of crosslinking between the conductive binder and the positive electrode active material is changed.

[0155] This example group was carried out with reference to Example 1, except that the degree of crosslinking between the conductive binder and the positive electrode active material was changed, as shown in Table 1-1, Table 1-2 and Table 1-3.

[0156] Example 8 Group

[0157] This group of examples is used to illustrate the impact produced when the weight proportion of carbon nanotubes with a length greater than 8 μm in all carbon nanotubes changes.

[0158] This example group is carried out with reference to Example 1, except that the weight proportion of carbon nanotubes with a length greater than 8 μm in all carbon nanotubes is changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.

[0159] Example 9 Group

[0160] This set of examples is used to illustrate the effects produced when the specific selection of the first modifier is changed.

[0161] This example group was carried out with reference to Example 1, except that the specific selection of the first modifier was changed, as shown in Table 1-1, Table 1-2 and Table 1-3.

[0162] Example 10 Group

[0163] This set of examples is intended to illustrate the effects that occur when the specific selection of polymer additives is varied.

[0164] This example group is carried out with reference to Example 1, except that the specific selection of the polymer additive is changed, as shown in Table 1-1, Table 1-2 and Table 1-3.

[0165] Example 11 Group

[0166] This group of embodiments is used to illustrate the impact when Y and / or Z are changed.

[0167] This embodiment group is carried out with reference to embodiment 1, except that Y and / or Z are changed, see Table 1-1, Table 1-2 and Table 1-3 for details.

[0168] Example 12 Group

[0169] This group of embodiments is used to illustrate the impact when X changes.

[0170] This embodiment group is carried out with reference to embodiment 1, except that X is changed, see Table 1-1, Table 1-2 and Table 1-3 for details.

[0171] Example 13 Group

[0172] This group of embodiments is used to illustrate the effects produced when the specific surface area of ​​carbon black and the oil absorption value of carbon black are changed.

[0173] This example group was carried out with reference to Example 1, except that the specific surface area of ​​carbon black and the oil absorption value of carbon black were changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.

[0174] Example 14 Group

[0175] This group of examples is used to illustrate the impact when the weight ratio of the carbonate solvent in the electrolyte changes.

[0176] This embodiment group is carried out with reference to the embodiment 1, except that the weight proportion of the carbonate solvent in the electrolyte is changed, see Table 1-1, Table 1-2 and Table 1-3 for details.

[0177] Comparative Example 1

[0178] The positive electrode active material (lithium cobalt oxide material (Dv50 particle size is 11.95 μm), the weight content of Al element in the lithium cobalt oxide material is 0.65%, the weight content of Mg element is 0.25%, the weight content of Zr element is 0.15%, the weight content of La element is 0.25%, and the weight content of Nb element is 0.15%), carbon black (acetylene black, specific surface area is 58 m 2 / g, oil absorption value is 327.1ml / 100g), conventional carbon nanotubes (including single-walled carbon nanotubes and multi-walled carbon nanotubes, the aspect ratio of multi-walled carbon nanotubes is 4672, the weight proportion of carbon nanotubes with a length greater than 8μm in all carbon nanotubes is 84.3%, the weight proportion of multi-arm carbon nanotubes in the positive electrode active material layer is Y 0.5%, and the weight proportion of single-ratio carbon nanotubes is Z 0.25%), and a binder (polyvinylidene fluoride) is fully mixed according to a mass ratio of 97.35:0.35:0.75:1.55, and N-methylpyrrolidone is added, and then fully stirred and vacuum defoamed to form a uniform positive electrode slurry, and the positive electrode slurry is coated on both sides of a positive electrode current collector (aluminum foil) with a thickness of 9μm to form a positive electrode active material layer. The surface density of the positive electrode sheet is 28.25mg / cm 2 Then it is dried in an oven at 110℃-135℃ and rolled (the compacted density is 4.0g / cm 3 ), cut to obtain a positive electrode sheet. The porosity of the positive electrode sheet is 18.27%, and the peeling force between the positive electrode current collector and the positive electrode active material layer is 21.56 N / m.

[0179] Comparative Example 2

[0180] The same method was used as in Example 1, except that conventional carbon nanotubes were used to replace the conductive binder. The porosity of the positive electrode sheet was 18.43%, and the peeling force between the positive electrode current collector and the positive electrode active material layer was 21.38 N / m.

[0181] Comparative Example 3

[0182] The method is carried out in accordance with Example 1, except that the second modifier is adjusted to hexadecyltrimethylammonium acetate, that is, the functional group in the bonding layer does not include an ester group. For details, see Table 1-1, Table 1-2 and Table 1-3.

[0183] Comparative Example 4

[0184] The method is carried out in accordance with Example 1, except that the second modifier is adjusted to propyl butyrate, that is, the functional groups in the bonding layer do not include amine groups and silane groups. For details, see Table 1-1, Table 1-2 and Table 1-3.

[0185] Comparative Example 5

[0186] The method is carried out in accordance with Example 1, except that the ratio of the number of amine groups to the number of ester groups is 2:1. For details, see Table 1-1, Table 1-2 and Table 1-3.

[0187] Comparative Example 6

[0188] The method is carried out in accordance with Example 1, except that the ratio of the number of amine groups to the number of ester groups is 6.5:1. For details, see Table 1-1, Table 1-2 and Table 1-3.

[0189] Table 1-1

[0190]

[0191]

[0192]

[0193]

[0194] * indicates the same as in Example 1; - indicates absence.

[0195] Table 1-2

[0196]

[0197]

[0198]

[0199]

[0200] * indicates the same as in Example 1; - indicates absence.

[0201] Table 1-3

[0202]

[0203]

[0204]

[0205] * indicates the same as in Example 1; - indicates absence.

[0206] Test Case

[0207] The positive electrode sheets and lithium-ion batteries obtained in the examples and comparative examples were tested as follows:

[0208] (1) Porosity test

[0209] The rolled positive electrode sheet is left to stand in a dry environment for more than 48 hours, and then cut into a certain size (for example, 60mm×60mm), and the thickness of the electrode sheet is measured with a micrometer, and the volume of the electrode sheet is calculated as V1; then the electrode sheet is placed in a test device, the gas valve is opened, helium is introduced, and the true volume V2 of the electrode sheet is tested; the porosity of the positive electrode sheet is obtained according to the formula (V1-V2) / V1*100%.

[0210] (2) Electrode resistance test

[0211] The rolled positive electrode sheet was directly tested for sheet resistance under a sheet resistance meter with a pressure of 0.4 MPa and a voltage of 1 V.

[0212] (3) Test of the state of positive electrode sheets at different compaction densities

[0213] The positive electrode sheets were rolled under different pressures to obtain different compaction densities (e.g., 4.05 g / cm 3 , 4.1g / cm 3 4.15g / cm 3 , 4.2g / cm 3 ) is wound around the positive electrode with a needle of 5 mm in diameter, and the state of the positive electrode is observed. If there is no crack at the edge, the result is indicated as "no abnormality"; if there is a crack at the edge, it is indicated as "crack at the edge".

[0214] (4) Test of residual liquid coefficient of electrolyte

[0215] The bare cell formed by winding is recorded as W1, and the electrolyte is injected into the bare cell, and the initial injection coefficient is set to 1.6. After the formation treatment, the excess electrolyte is separated, and the weight of the cell at this time is recorded as W2. After sorting, the battery is charged to the upper limit voltage (4.5V) at a constant current of 0.2C, and then charged to 0.02C at a constant voltage of 4.5V, and allowed to stand for 5 minutes; then discharged to 3.0V at a constant current of 0.2C, allowed to stand for 5 minutes, and the discharge capacity is measured to be Q. The residual liquid coefficient of the electrolyte is obtained according to the formula 1000×(W2-W1) / Q.

[0216] (5) Cyclic performance test

[0217] Place the lithium-ion battery in a 25°C environment and let it stand for 0.5 hours. When the battery temperature is 25±2°C, measure the thickness of the battery at this time as H1. Charge it to the upper limit voltage (4.5V) at a constant current of 0.5C, then charge it to 0.05C at a constant voltage of 4.5V and let it stand for 5 minutes; then discharge it to 3.0V at a constant current of 0.5C and let it stand for 5 minutes. This is a charge and discharge cycle, and the charge and discharge cycle is 500 times. The highest discharge capacity of the first three cycles is recorded as the initial capacity Q1, the discharge capacity of the 500th cycle is Q2, and the thickness of the battery after 500 test cycles is H2; calculate the battery capacity retention rate = Q2 / Q1×100%.

[0218] The thickness expansion rate of the battery = ((H2-H1) / H1) x 100%.

[0219] (6) Lithium precipitation

[0220] Place the lithium-ion battery in a 25°C environment and let it stand for 0.5 hours. When the battery temperature is 25±2°C, measure the thickness of the battery at this time as H1. Charge it to the upper limit voltage (4.5V) at a constant current of 0.5C, then charge it to 0.05C at a constant voltage of 4.5V and let it stand for 5 minutes; then discharge it to 3.0V at a constant current of 0.5C and let it stand for 5 minutes. This is a charge and discharge cycle, and the charge and discharge cycle is 100 times. After 100 cycles of observation, disassemble the battery and check the status of the negative electrode sheet. If there is no lithium precipitation and purple spots, it means "no abnormality". If lithium precipitation and / or purple spots occur, and the area of ​​lithium precipitation and / or purple spots accounts for less than 15% of the total area of ​​the negative electrode sheet, it means "slight lithium precipitation" or "slight purple spots". If lithium precipitation and / or purple spots occur, and the area of ​​lithium precipitation and / or purple spots accounts for ≥15% of the total area of ​​the negative electrode sheet, it means "purple spots, lithium precipitation".

[0221] Table 2

[0222]

[0223]

[0224]

[0225] As can be seen from Table 2, through the comparative examples and the embodiments, it can be seen that the positive electrode sheet of the embodiment is in a better state at different compaction densities, the resistance of the electrode sheet is lower, the residual liquid coefficient of the battery made from the positive electrode sheet of the embodiment is higher, the cycle capacity retention rate is higher, the expansion rate is lower, and the state of the electrode surface after 100 cycles is better, indicating that by arranging a three-dimensional network skeleton in the positive electrode active material layer and controlling the ratio of the number of amino groups and / or silane groups to the number of ester groups in the bonding layer of the three-dimensional network skeleton, the wettability of the battery electrolyte to the positive electrode sheet and the conductivity of the positive electrode sheet are improved, the cycle expansion rate of the battery is reduced, and the cyclability and safety performance of the battery are improved.

[0226] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, the positive electrode active material layer includes a three-dimensional network skeleton and a positive electrode active material located in the three-dimensional network skeleton, the three-dimensional network skeleton is formed by a conductive adhesive, the conductive adhesive includes carbon nanotubes and a bonding layer located on at least a portion of the surface of the carbon nanotubes, the bonding layer includes an ester group, an amine group and a silane group, wherein the ratio of the number of the amine groups and / or the silane groups to the number of the ester groups is (3-6):

1.

2. The positive electrode sheet according to claim 1, wherein: The bonding layer further comprises one or more of the following functional groups: methyl, carboxyl, hydroxyl; And / or, the carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes; And / or, the aspect ratio of the conductive adhesive is ≥10, preferably ≥1000; and / or, the degree of crosslinking between the conductive binder and the positive electrode active material is ≥ 0.1, preferably 0.1-3, more preferably 0.15-0.5; And / or, the positive electrode active material layer further includes carbon black, and the carbon black includes one or more of furnace black, acetylene black and Ketjen black.

3. The positive electrode sheet according to claim 2, wherein: The positive electrode sheet satisfies the following relationship: 0.25%≤Z+Y≤2.5%, and / or, 2≤Y / Z≤5, and / or, X=0.82 / (Y×W / 1000), wherein X is the weight proportion of carbon black in the positive electrode active material layer, in %, Y is the weight proportion of multi-walled carbon nanotubes in the positive electrode active material layer, in %, Z is the weight proportion of single-walled carbon nanotubes in the positive electrode active material layer, in %, and W is the aspect ratio of multi-walled carbon nanotubes; And / or, the specific surface area of ​​the carbon black is 30m 2 / g-150m 2 / g, preferably 50m 2 / g-80m 2 / g; And / or, the oil absorption value of the carbon black is ≥300 ml / 100 g, preferably 320 ml / 100 g-360 ml / 100 g.

4. The positive electrode sheet according to claim 3, wherein: The weight proportion X of carbon black in the positive electrode active material layer is 0.2%-1%, preferably 0.3%-0.6%; And / or, the weight proportion Y of the multi-walled carbon nanotubes in the positive electrode active material layer is 0.3%-0.8%, preferably 0.4%-0.6%; And / or, the weight proportion Z of the single-walled carbon nanotubes in the positive electrode active material layer is 0.05%-0.5%, preferably 0.1%-0.3%; And / or, the aspect ratio W of the multi-walled carbon nanotubes is 1000-10000; preferably 2000-5000.

5. The positive electrode sheet according to any one of claims 1 to 4, wherein: The thickness of the tube wall of the conductive adhesive is 6nm-7nm; And / or, the average diameter of the conductive adhesive is 2nm-10nm; and / or, the average length of the conductive adhesive is 13 μm-17 μm; and / or, the weight proportion of the carbon nanotubes with a length of >8 μm in all carbon nanotubes is ≥50%, preferably 70%-90%; And / or, the ratio of the thickness of the adhesive layer to the tube diameter of the conductive adhesive is 0.1-0.4, preferably 0.15-0.

25.

6. The positive electrode sheet according to any one of claims 1 to 4, wherein: The positive electrode active material layer also includes a first modifier and a polymer additive; Preferably, the first modifier includes one or more of hexadecyltrimethylammonium tetrafluoroborate, N-(coconut alkyl)-N,N,N-trimethylammonium methyl sulfate, cocamidopropyl betaine, hexadecyltrimethylammonium acetate and hexadecyltrimethylammonium nitrate; Preferably, the polymer additive comprises one or more of polyamide, modified polyamide, and polyamide derivatives; Preferably, the molecular weight of the polymer additive is 1000000 g / mol-2000000 g / mol, preferably 1200000 g / mol-1500000 g / mol.

7. The positive electrode sheet according to claim 6, wherein: Based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 96%-98.7%, the weight content of the conductive binder is 0.25%-1.5%, the weight content of the first modifier is 0.25-1.5%, and the weight content of the polymer additive is less than 1%.

8. The positive electrode sheet according to any one of claims 1 to 4, wherein: The positive electrode active material includes lithium cobalt oxide material; Preferably, the lithium cobalt oxide material includes a doping element, and the doping element includes one or more of Mg, Zr, La, Al, and Nb; Preferably, the median particle size Dv50 of the lithium cobalt oxide is 8 μm-15 μm.

9. The positive electrode sheet according to any one of claims 1 to 4, wherein: The bonding layer in the conductive adhesive is formed by modifying the carbon nanotubes with a second modifier, wherein the second modifier includes one or more of diethyl adipate, diethyl dimethylmalonate, diethyl suberate, dimethyl malonate, dimethyl suberate, methyl valerate, propyl butyrate, n-dodecyltrimethoxysilane, silane coupling agent, trimethylsilane, hexadecyltrimethylammonium tetrafluoroborate, N-(coconut alkyl)-N,N,N-trimethyl methylammonium sulfate, cocamidopropyl betaine, hexadecyltrimethylammonium acetate and hexadecyltrimethylammonium nitrate; And / or, the porosity of the positive electrode sheet is 20%-35%; And / or, the peeling force between the positive electrode current collector and the positive electrode active material layer is ≥90 N / m.

10. A battery, characterized in that: The battery comprises the positive electrode sheet according to any one of claims 1 to 9.

11. The battery according to claim 10, wherein The battery further comprises an electrolyte, wherein the electrolyte comprises a carbonate solvent; Preferably, the carbonate solvent includes one or more of ethylene carbonate, propylene carbonate and dimethyl carbonate; Preferably, based on the total weight of the electrolyte, the weight content of the carbonate solvent is 40%-80%, preferably 50%-70%.

Citation Information

Patent Citations

  • Positive plate of lithium iron phosphate battery, fabrication method thereof and lithium iron phosphate battery

    CN106129330A

  • Low-temperature lithium battery

    CN113471512A

  • Fast-charging polymer lithium ion battery

    CN113555540A

  • Polymer-based negative current collector and preparation method thereof

    CN115763696A

  • Positive electrode sheet, secondary battery, and electronic device

    CN116111043A

Cited By

  • Conductive carbon black, positive pole piece, electrochemical device and electronic device

    CN119890315A